Ordered b-metric spaces and Geraghty type contractive mappings - Chandok, Sumit C.; Jovanović, Mirko S.; Radenović, Stojan N. (Vojnotehnički glasnik / Military Technical Courier, 2017)
The paper shows a new approach to proving the recent fixed point results in ordered b-metric as well as ordered metric spaces, established by several authors, with much shorter and nicer proofs. An example is given to illustrate our results.